Analysis of Low Carbohydrate High Fat Formula on Length of Days of Hospitalization for Confirmed Covid-19 Patients with Pneumonia at RSMH Palembang in 2021 - Septa Clara Astiyah; Sri Hartati; Mulaiha (Jurnal RSMH Palembang, 2021)
Analysis of RKTL Formula Feeding toward the Length of Stay (LOS) for COVID-19 Confirmed Patients with Pneumonia as Comorbidity. COVID-19 is one of the latest respiratory virus as known as SARS-CoV-2 which caused acute respiratory syndrome and can lead to death. Pneumonia occurs as one of the COVID-19 comorbidities that occurs at day 5-6 to day 14, indicated by infection and fever which progressively weaken respiratory and immunity system. One of the nutritional therapy for COVID-19 confirmed patients with pneumonia as comorbidity is RKTL (Rendah Karbohidrat Tinggi Lemak) formula which can accelerate recovery, increase O2 level, and decreasing CO2 production so that it will reduce the length of stay (LOS). The aim of the study was to analyze the effect of RKTL formula diet toward LOS for COVID-19 patients with pneumonia as comorbidity. This was a true-experimental study with parallel design clinical trial in COVID-19 isolation ward at RSMH Palembang during May-August 2021. The collected data was primary data consists of before and after intervention as long as the subjects being hospitalized then analyzed univariate to find out the distribution of frequency presented by simple boxplot graph. The study reported that there were differences in average for the LOS among three subject group. The control group has 11 days for the Average Length of Stay (ALOS), where case group XI whom given RKTL formula feeding 1x/day had the Average Length of Stay (ALOS) for 10 days and case group X2 whom given RKTL formula feeding 3x/day had the Average Length of Stay (ALOS) for 7 days. It can be concluded that there was an effect of RKTL formula diet toward the Length of Stay (LOS) for COVID-19 confirmed patients with pneumonia as comorbidity.